Middle meningeal artery embolization as an adjuvant treatment to surgery for symptomatic chronic subdural hematoma: a pilot study assessing hematoma volume resorption. (20th December 2019) - Ng, Sam; Derraz, Imad; Boetto, Julien; Dargazanli, Cyril; Poulen, Gaëtan; Gascou, Gregory; Lefevre, Pierre-Henri; Molinari, Nicolas; Lonjon, Nicolas; Costalat, Vincent
Abstract : Background: Chronic subdural hematoma (CSDH) is a common condition requiring surgical treatment; however, recurrence occurs in 15% of cases at 1 year. Middle meningeal artery (MMA) embolization has recently emerged as a promising treatment to prevent CSDH recurrence. Objective: To investigate the effect of MMA embolization on hematoma volume resorption (HVR) after surgery in symptomatic patients. Methods: From April 2018 to October 2018, participants with CSDH requiring surgery were prospectively randomized in a pilot study, and received either surgical treatment alone (ST group) or surgery and adjuvant MMA embolization (ST+MMAE group). The primary outcome was HVR measured on the 3 month CT scan compared with the immediate pre-embolization CT scan. Secondary outcomes were clinical recurrence of CSDH and safety measures. Results: 46 patients were randomized and 41 of these achieved a 3 month follow-up . Twenty-one patients received MMA embolization. At 3 months, the HVR from postsurgical level was higher in the ST+MMAE group (mean difference 17.5 mL, 95% CI 3.87 to 31.16 mL; p=0.015). Two participants presented a CSDH recurrence (one in each group). One patient died (ST group). No MMA embolization-related adverse events were reported. Conclusion: The addition of MMA embolization to surgery led to an increase in CSDH resorption at 3 months. One recurrence of CSDH was reported in each group, and there were no treatment-related complications.